Re-identification of the material of Neocallichirus maryae Karasawa, 2004 from Ceará, northeastern Brazil, with the first record of N. cacahuate Felder & Manning, 1995 in the southwestern Atlantic - Pachelle, Paulo P.g.; Anker, Arthur; Bezerra, Luis E.a. (Zootaxa, 2017)
In July 2016, an important regional checklist entitled “Decapod crustaceans from the state of Ceará, northeastern Brazil: an updated checklist of marine and estuarine species, with 23 new records” was published in the journal Zootaxa (Pachelle et al. 2016). A few days after publication of this monograph, two of our colleagues specialised in the taxonomy of ghost and mud shrimps (Axiidea and Gebiidea), Dr Mônica Botter-Carvalho (UFRPE) and Dr Peter C. Dworschak (NHMW), informed us that the material reported under Neocallichirus maryae Karasawa, 2004 appeared to contain more than one species. Their comments were based on examination of colour photographs showing several specimens identified as N. maryae in Pachelle et al. (2016)’s figure 21. This prompted a re-examination of the material from Ceará identified as N. maryae, including all specimens reported by Pachelle et al. (2016). Despite the fact that most of them were correctly identified as N. maryae, two individuals (MZUSP 32610, 32615) were re-identified as Sergio guassutinga (Rodrigues, 1971) [as indeed suggested by M. Botter-Carvalho and P.C. Dworschak] and Neocallichirus cacahuate Felder & Manning, 1995, respectively. The former species is a new record for the state of Ceará, whilst the latter species represents a new record not only for Ceará, but also for Brazil and the southwestern Atlantic.